Analysis Of Village Original Income (Pades) Of Sukarami Village (Village Original Income Strategy Study) - Imanda, Antonia; C. Kader, Bando Amin; Yolani, Lendra; Luki, Luki (Utan Kayu Publishing, 2023)
This study aims to evaluate the strategies used to increase Village Original Income (PADes) in Sukarami Village, Taba Penanjung District, Central Bengkulu Regency. This study uses a descriptive qualitative method with data collection techniques in the form of observation, interviews, and documentation studies. Informants in the study included village officials, managers of Village-Owned Enterprises (BUMDes), and the surrounding community. The data analysis process was carried out using the SWOT (Strengths, Weaknesses, Opportunities, Threats) approach. The research findings reveal that the strengths of PADes management in Sukarami Village include central government funding support, the availability of adequate technology, and the active involvement of local human resources. On the other hand, there are a number of weaknesses such as budget limitations and low levels of education of several managers. However, strategic opportunities remain open through the development of village businesses and high community participation. Based on these findings, this study recommends increasing human resource capacity and diversifying village businesses as an effort to maximize the role of PADes in village development.